CELL SURFACE IMMUNOGLOBULIN : VII. SYNTHESIS, SHEDDING, AND SECRETION OF IMMUNOGLOBULIN BY LYMPHOID CELLS OF GERM-FREE MICE - Vitetta, Ellen S. (The Rockefeller University Press, 1974)
Lymphoid cells from the spleen, lymph nodes, and thoracic duct of axenic and control mice were incubated with [3H]tyrosine and synthesis and secretion of protein and Ig studied. It was found that only IgM was synthesized by cells from axenic mice whereas cells from control mice also synthesized IgG. Splenocytes from both axenic and control mice had 8S IgM on their surface. Radiolabeled splenocytes from axenic mice were incubated to determine the kinetics of release of 125I-labeled cell surface IgM and [3H]tyrosine-labeled IgM. Cell surface IgM was shed as 8S with an initial half-life of release of 5–8 h whereas [3H]tyrosine-labeled Ig was secreted as 19S with an initial half-life of 2–3 h. These findings suggest that two independent pathways are involved. It is suggested that small lymphocytes shed 8S IgM and plasma cells secrete 19S IgM. It was observed that lymphoid cells from axenic mice synthesize a higher proportion of IgM relative to total protein. Electron microscopic examination of splenocytes from such mice revealed a markedly higher proportion of plasma cells and a paucity of lymphoblasts compared to controls. It was suggested, therefore, that axenic mice lack a population of stimulated T cells which can induce a switch from IgM to IgG synthesis and which is capable of suppressing IgM synthesis. Lymphoid cells from axenic mice synthesize and secrete less protein that coprecipitates with antigen-antibody complexes.